Surgical Treatments of Epilepsy - Ahmad, Shahjehan; Khanna, Ryan; Sani, Sepehr (Seminars in Neurology, 2020)
Nearly 30% of epilepsy patients are refractory to medical therapy. Surgical management of epilepsy is an increasingly viable option for these patients. Although surgery has historically been used as a palliative option, improvements in technology and outcomes show its potential in certain subsets of patients. This article reviews the two main categories of surgical epilepsy treatment—resective surgery and neuromodulation. Resective surgery includes temporal lobe resections, extratemporal resections, laser interstitial thermal therapy, and disconnection procedures. We discuss the three main types of neuromodulation—vagal nerve stimulation, responsive neurostimulation, and deep brain stimulation for epilepsy. The history and indications are explored for each type of treatment. Given the myriad types of resection and neuromodulation techniques, patient selection is reviewed in detail, with a discussion on which patients are most likely to benefit from different treatment strategies. We also discuss outcomes with examples of the pertinent landmark trials and their results. Finally, complications and surgical technique are reviewed. As new indications emerge and patient selection is refined, surgical management will continue to evolve as an adjuvant therapy for epileptic patients.
Keywords: epilepsy surgery; resection; neuromodulation